Hezekiah in history and tradition - Young, Robb Andrew (Leiden ; Boston : Brill, 2012)
This study draws upon the biblical books of Kings, First Isaiah and Chronicles, in conjunction with Assyrian records and ancient Near Eastern archaeology, in order to provide an updated historical reconstruction of the influential Judean monarch Hezekiah.
Chapter Eight The Historical Reliability of 2 Chr 31-328.1. The Reform and the Portions (2 Chr 31); 8.1.1. The Reform; 8.1.2. Distribution of the Portions; 8.1.3. Historical Analysis of the Portions; 8.2. The Invasion of Sennacherib (2 Chr 32); 8.2.1. Hezekiah's Defensive Measures (vv 3-6); 8.2.2. Hezekiah's Achievements (vv 27-30); 8.3. Conclusion; Chapter Nine Hezekiah as a Second David/Solomon; 9.1. The Dynastic Promises to David and Solomon; 9.1.1. Conditional and Unconditional Material; 9.1.2. The Depiction of Solomon; 9.2. The Pro-Solomonic Source of Chronicles.
Includes bibliographical references and indexes.
Master record variable field(s) change: 630
Keywords: Hezekiah, -- King of Judah; Bible. -- Criticism, interpretation, etc; Bible. -- Criticism, interpretation, etc; Bible. -- Criticism, interpretation, etc; Bible. -- History of Biblical events; Bible. -- History of contemporary events; Bible. -- Criticism, interpretation, etc; Bible. -- Criticism, interpretation, etc; Bible. -- Criticism, interpretation, etc; Jews -- History -- 953-586 B.C.; Hezekiah, King of Judah; Jews -- History -- 953-586 B.C.; Religion; RELIGION -- Biblical Studies -- Old Testament; Electronic books